Connective tissue growth factor-targeting DNA aptamer suppresses pannus formation as diagnostics and therapeutics for rheumatoid arthritis - Wu, Gan; Liu, Can; Cao, Ben; Cao, Zelin; Zhai, Haige; Liu, Bin; Jin, Shengwei; Yang, Xinyu; Lv, Chen; Wang, Jianguang (Frontiers in Immunology, 2022)
Connective tissue growth factor (CTGF) has been recently acknowledged as an ideal biomarker in the early disease course, participating in the pathogenesis of pannus formation in rheumatoid arthritis (RA). However, existing approaches for the detection of or antagonist targeting CTGF are either lacking or unsatisfactory in the diagnosis and treatment of RA. To address this, we synthesized and screened high-affinity single-stranded DNA aptamers targeting CTGF through a protein-based SELEX procedure. The structurally optimized variant AptW2-1-39-PEG was characterized thoroughly for its high-affinity (KD 7.86 nM), sensitivity (minimum protein binding concentration, 2 ng), specificity (negative binding to other biomarkers of RA), and stability (viability-maintaining duration in human serum, 48 h) properties using various biochemical and biophysical assays. Importantly, we showed the antiproliferative and antiangiogenic activities of the aptamers obtained using functional experiments and further verified the therapeutic effect of the aptamers on joint injury and inflammatory response in collagen-induced arthritis (CIA) mice, thus advancing this study into actual therapeutic application. Furthermore, we revealed that the binding within AptW2-1-39-PEG/CTGF was mediated by the thrombospondin 1 (TSP1) domain of CTGF using robust bioinformatics tools together with immunofluorescence. In conclusion, our results revealed a novel aptamer that holds promise as an additive or alternative approach for CTGF-targeting diagnostics and therapeutics for RA.